KESIAPAN GURU DALAM MENGIMPLEMENTASIKAN KURIKULUM MERDEKA BELAJAR PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SMP KOTA SEMARANG - Dimas Khijri Saputra; Ahmad Maghfurin; Nasirudin Nasirudin (Taklim : Jurnal Pendidikan Agama Islam, 2023)
AbstactThis study shows that: 1). The readiness of PAI teachers in implementing the independent learning curriculum in Islamic Religious Education and Moral Education subjects at SMP Negeri 1 Semarang City has cognitively understood the concept of independent learning curriculum and is affectively very optimistic because the Merdeka Learning platform provides opportunities for teachers to continue learning and developing their competencies and provide opportunities for teachers and education staff to be able to obtain quality training materials by accessing them independently. Meanwhile, institutionally, teachers are supported by schools from the aspect of facilities and infrastructure. Meanwhile, the readiness of PAI teachers at Nasima Middle School, Semarang City, cognitively understands the concept of the Free Learning curriculum and is affectively very enthusiastic because the independent learning curriculum has many advantages. However, in terms of skills, teachers experience problems due to minimal experience, limited references and difficult time management. 2). Implementation of the Freedom to Learn curriculum in the subject of Islamic Religious Education and Characteristics by Islamic Religious Education teachers at SMP Negeri 1 Semarang City applying Problem based learning, Experiments, Peer Teaching (peer tutors), and Design in the Merdeka Learning curriculum. The assessment applied is an assessment at the end of each discussion material by using a written test (daily tests), practice, presentation of a material, and performance. There is a remedial program for students who do not reach the KKM and an enrichment program for students who have reached the KKM as reinforcement. Meanwhile, the implementation of the Independent Curriculum for learning in Islamic Religious Education and Moral Education subjects at Nasima Middle School in Semarang City applies the Problem Based Learning, Project-Based and Discussion methods. While the assessment focuses on strengthening formative assessments and using the results of the assessment to design learning according to student achievement stages.Keyword: PAI Teacher Readiness, Independent Learning Curriculum AbstrakKajian ini menunjukkan bahwa: 1). Kesiapan guru PAI dalam mengimplementasikan kurikulum merdeka belajar pada mata pelajaran Pendidikan Agama Islam dan Budi Pekerti di SMP Negeri 1 Kota Semarang secara kognitif telah memahami konsep kurikulum merdeka belajar dan secara afektif sangat optimis karena platform Merdeka Belajar memberikan kesempatan guru untuk terus belajar serta mengembangkan kompetensinya dan memberikan kesempatan kepada guru dan tenaga kependidikan untuk dapat memperoleh materi pelatihan yang berkualitas dengan mengaksesnya secara mandiri. Sedangkan secara kelembagaan, guru  disupport oleh sekolah dari aspek sarana dan prasarana. Sedangkan, kesiapan guru PAI di SMP Nasima Kota Semarang secara kognitif telah memahami konsep kurikulum Merdeka Belajar dan secara afektif sangat antusias karena kurikulum merdeka belajar banyak memiliki kelebihan. Namun dari sisi skill, guru mengalami kendala karena pengalaman yang masih minim, referensi yang terbatas dan manajemen waktu yang tidak mudah. 2).Implementasi kurikulum Merdeka Belajar pada mata pelajaran Pendidikan Agama Islam dan Budi Pekerti oleh guru Pendidikan Agama Islam di SMP Negeri 1 Kota Semarang menerapkan Problem based learning, Percobaan, Peer Teaching (tutor sebaya), dan Perancangan dalam kurikulum Merdeka Belajar. Adapun penilaian yang diterapkan adalah penilaian setiap akhir materi pembahasan dengan menggunakan tes tertulis (ulangan harian), praktek, persentasi suatu materi, dan unjuk kerja. Terdapat program remedial bagi peserta didik yang tidak mencapai KKM dan program pengayaan bagi siswa yang sudah mencapai KKM sebagai menguatan. Sedangkan, implementasi Kurikulum Merdeka belajar pada mata pelajaran Pendidikan Agama Islam dan Budi Pekerti di SMP Nasima Kota Semarang menerapkan metode Problem Based Learning, Berbasis Project dan Diskusi. Sedangkan penilaiannya berfokus pada penguatan asesmen formatif dan penggunaan hasil asesmen untuk merancang pembelajaran sesuai tahap capaian siswa.Kata Kunci: Kesiapan Guru PAI, Kurikulum Merdeka Belajar